Sindroma Steven-Johnson pada Anak Akibat Penggunaan Carbamazepin: Sebuah Laporan Kasus: Steven-Johnson Syndrome in Children due to Carbamazepine Use: a case Report - Ika Lusiana; Felix Nathan Trisnadi (Jurnal Surya Medika (JSM), 2023)
Steven-Johnson syndrome is rare occurance. In children, the incidence of Steven Johnson Syndrome (SJS) is lower than adults. Steven Johnson Syndrome is often caused by a hypersensitivity reaction to drugs, including carbamazepine. Correct and appropriate therapy management will support the improvement of conditions and reduce mortality